KONSEP PERENCANAAN STRATEGIS DALAM MENINGKATKAN MUTU PENDIDIKAN - Yuli Anggraeni; Lela Iman Ningrum; Istikomah; Ngurah Ayu Nyoman Murniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Strategic planning of education is a systematic process that involves all components of the school in formulating a clear vision, mission, goals, and strategies to achieve sustainable improvement in the quality of education. This concept emphasizes the importance of careful planning, involving all stakeholders, and being results-oriented. With strategic planning, schools can implement it in line with the expected goals. In order to support its existence, schools need effective strategic planning. In reality, there are still schools that do not have a strategic plan to support proper and programmatic school management. Meanwhile, the purpose of writing this article is to find out the process of implementing a strategic plan in improving the quality of education in schools. The method used in this study is a literature study. focusing on collecting data based on theories from various literature sources relevant to the research topic. Some of the stages that can be carried out by schools in strategic planning in improving the quality of education are environmental analysis, strategy formulation and strategy formulation, implementation of strategic plans in school management, evaluation and control of strategies School efforts to improve the quality of education include the following: Optimizing the implementation of the Curriculum, Improving the quality of educators, Improving the quality of learning Developing quality and quantity Learning Facilities It is recommended that each level of education develop a strategic planning model to improve the quality of education, so that it can produce the right strategy in accordance with the vision and mission, and enable the achievement of goals on target. In addition, improving the quality of educators and education personnel, which are considered strategic resources in schools, needs to be supported by various relevant trainings to improve the quality of education.